Merdeka Belajar Kampus Merdeka (MBKM) Collaboration with BUMDes Sari Dewi, Maguwoharjo, Sleman - Zuhrohtun, Zuhrohtun; Heriningsih, Sucahyo; Sunaryo, Kunti; Sriyono, Sriyono (RSF Conference Series: Business, Management and Social Sciences, 2021)
One of the implementations of Merdeka Belajar Kampus Merdeka (MBKM) program at UPN "Veteran" Yogyakarta, contained in the Rector's Regulation No. 13 of 2020 concerning the Implementation of MBKM Program at Universitas Pembangunan Nasional "Veteran" Yogyakarta on September 2, 2020, is the program of village project. This article is the result of applied research on the MBKM program of the Accounting Department in Maguwoharjo village, Sleman Regency. MBKM programs are designed with various financial management assistance activities with one of the partners, which is Badan Usaha Milik Desa (BUMDes) in Maguwoharjo by lecturers and an internship program for students as a form of off-campus learning activities, which is the program of village project. The purpose of the village project is to increase the achievement of the Main Performance Indicators (MPI) of Higher Education number 3 (lecturers doing activities outside campus) and MPI number 5 (performance results of lecturers and students are recognized and can be used by the community). The results of this study indicate that for the implementation of MBKM with the Village Project, among others are: 1. It has been identified early related to the implementation of learning activities outside the campus (in BUMDes), 2. Identified the potential of BUMDes that can be developed in village project of MBKM activities by students, 3. Identified the equivalent value of student internships participating in the village project.